Kedudukan Dan Peran Badan Penyiaran Hindu Dalam Pembinaan Kehidupan Keagamaan Di Indonesia - Untung Suhardi; Lusiana Oktaviani; I Made Biasa; I Wayan Arif Sugiarta; Indra Prameswara (Sekolah Tinggi Agama Buddha Nalanda, 2020)
This research was that the theme of the place of the Broadcasting Board of Hinduism in Indonesia. This research is qualitative descriptive design to outline the position associated with Hindu Broadcasting Agency (BPH). This research was conducted at the Center BPH, BPH Banten and BPH DKI Jakarta. The process of collecting the data, through several namely: observation, interviews, literature, and documentation. The process of collecting data in this study through several stages: observation, interviews, and documentation. Related to that this research is a field data into the underlying data in the study, the authors in this case finding and determine the sources that are considered helpful in providing information to then be processed through a technique to achieve the validity of the data that is triangulation (observation, interviews, and literature) and photographs or other supporting documents. This study refers to the position of the Broadcasting Agency in the Hindu religious development in Indonesia. How BPH development support for the Hindus through electronic media and the mass media. BPH is expected through broadcasting products more varied and also coaching Hindus can be improved. Thus, knowledge of Hindu teachings can be conveyed and understood by Hindus